Genotypification, in vitro toxigenic evaluation, and antibiotic sensitivity of Escherichia coli strains isolated from diarrheic and fatal cases in neonatal alpacas - Luna E., Luis (2012)
Clinical rectal diarrheic swabs (n=27) and pathological intestinal contents (n=24) from 51 alpacas between 1 to 7 weeks of age were used to isolate and genotype Escherichia coli, and to test for antimicrobial sensibility. All the E. coli isolates, confirmed by the API system, were genotyped by Multiplex PCR to determine the presence of virulence genes: stx1 and stx2 (shigatoxin 1 and 2), eae (intimin), bfp (Bundle-Forming Pili), lt (heat-labile toxin), sta and stb (heat-stable toxin A and B), in enterohemorrhagic (EHEC), enteropathogenic (EPEC) or enterotoxigenic (ETEC) E. coli strains. Positive stx1 and stx2 strains were tested on Vero cells for verocytotoxicity, and all isolates were tested for antimicrobial sensibility to the eight most frequent used antibiotics in Andean livestock. Microbiological and molecular analysis revealed the presence of pathogenic E. coli strains in 19/27 (70.4%) of the clinical diarrhea cases and 11/24 (45.8%) of the pathological intestinal content samples. In crias suffering from diarrhea, 94.7% (18/19) of the pathogenic isolates were EPEC strains while the remaining was stx2 EHEC with a low expression of verocytoxic activity (1:16). Eleven of the 18 EPEC were positive for both eae and bfp, while the remaining seven were eae positive only. Six of the 11 (54.5%) isolates from intestinal contents were EPEC eae positive only, while the remaining five (45.5%) were EHEC isolates. Three of the 5 EHEC isolates tested positive to stx1 with two expressing high verocytotoxicity, while the fourth tested positive for stx2 with similar high expression of verocytotoxicity, and the fifth was positive for both stx1 and stx2 genes but could not be evaluated the verocytotoxicity. Eighty percent of the pathogenic and non-pathogenic E. coli strains showed resistance to neomycin, and 25% to oxytetracycline. These results indicate that alpacas harbor potentially pathogenic E. coli strains that might cause clinical and fatal intestinal disorders in young animals.